Microtwinning in the nickel-based superalloy CM247LC during compression tests. Issue 22 (17th November 2022) - Zhang, P.; Yuan, Y.; Gao, Z.H.; Li, J.; Niu, Q.; Shi, X.B.; Zhou, Y.L.; Gu, Y.F.
ABSTRACT: We have studied the variations in the compressive yield strength and deformation modes of the directionally solidified nickel-based superalloy CM247LC with temperature. It is found that the yield strength of the alloy only fluctuates in a small range with temperature when the deformation temperature is below 800 °C. Whereas, as the temperature is raised further, the strength decreases dramatically. After a small plastic strain, the substructures in the alloy are investigated using transmission electron microscope. It is startling to find large numbers of APB (anti-phase boundary)-coupled a /2 < 011 > dislocation pairs, isolated stacking faults and extended stacking faults as well as microtwins in the alloy at temperatures between 25 and 950 °C. Whereas, at 1000 °C, although dislocations bypassing γ′ particles via climb dominates the plastic deformation, two matrix dislocations with different Burgers vectors collectively penetrating γ′ particles, APB shearing and shearing of γ′ particles by partial dislocations also take place during plastic deformation. On the ground of the microstructural observations, correlation between the flow stress and deformation modes is discussed.